Effect of Daily Consumption of Orange Juice on the Levels of Blood Glucose, Lipids, and Gut Microbiota Metabolites: Controlled Clinical Trials - Lima, Ana Carolina Delgado; Cecatti, Clara; Fidélix, Melaine Priscila; Adorno, Maria Angela Tallarico; Sakamoto, Isabel Kimiko; Cesar, Thais Borges; Sivieri, Katia (Journal of medicinal food, 2019)
Ingestion of bioactive compounds, such as hesperidin and naringin, found in citrus fruits and orange juice, can improve the homeostasis of gut microbiota. A controlled clinical study with temporal series intergroup design with 10 apparently healthy women (28.5 ± 8.4 years, 24.1 ± 3.3 kg/m ) were evaluated after continuous consumption of commercial pasteurized orange juice for 2 months. Samples of blood serum and stool were collected at basal time and periodically during the experiment for biochemical and microbiology assays. Intestinal microbiota was evaluated for total anaerobic bacteria, Lactobacillus spp., Bifidobacterium spp., and Clostridium spp. An independent culture evaluation was performed using Denaturing Gradient Gel Electrophoresis (DGGE). The pH, ammonium (NH ), and short-chain fatty acids (SCFAs) were evaluated for microbial metabolism. The results showed that daily intake of orange juice did not change women's body composition, but improved blood biochemical parameters, such as low-density lipoprotein-cholesterol, glucose, and insulin sensitivity. Orange juice positively modulated the composition and metabolic activity of microbiota, increasing the population of fecal Bifidobacterium spp. and lactobacillus spp. Polymerase chain reaction-DGGE of microbiota showed similar composition of total bacteria, and microbial metabolism showed a reduction of ammonia and an increase of the production of SCFAs. These results suggested that a daily consumption of orange had a positive effect on the intestinal microbiota and metabolic biomarkers of young women, which may be an effective alternative for a healthy drink.